The Analysis of Students’ School Burnout Level and Academic Achievement on The Science Management Subject - Masruroh, Masruroh; Nawafilah, Nur Qomariyah; Anggraini, Erry (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
School burnout can be a vulnerable thing experienced by students during learning process. This study is purposed to describe the difference of students’ academic achievement in management science subject based on school burnout level. This study is quantitative descriptive study. Students’ school burnout level data was gathered using school burnout inventory using Google form questionnaire, while students’ academic achievement data was attained from students’ final score on management science subject. Data was taken from 83 respondents who were actively participate in management science subject. Data of students’ school burnout then was categorized into low and high level of school burnout. The academic achievement from each group of school burnout level then was compared and analyzed using t-test on R software. The result showed that 52% students have low school burnout level and the other 48% have high school burnout level. The average of students’ academic achievement from low and high levels school burnout group were 78.0 and 75.7 sequentially. The p-value generated from t-test was 0.1644, greater than 0.05. Thus, it can be concluded that there was no significant difference on students’ academic achievement between low and high level of school burnout group.